2000
DOI: 10.1177/016555150002600403
|View full text |Cite
|
Sign up to set email alerts
|

Information technology in Nigerian federal agencies: problems, impact and strategies

Abstract: The paper assesses the perceptions of personnel of Nigerian federal public agencies about obstacles to information technology (IT) use, the impact of computers on agency departments and tasks and about approaches to IT human resource development. The analyses are based on data from a questionnaire survey of the personnel of ministries, parastatals and Government-controlled banks who participated in various training programmes of the (Nigerian) National Centre for Economic Management and Administration (NCEMA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…This might explain our findings which established that training in statistical analysis was the skill most sought-after by the participants (69.0 %). These findings coincide with various studies that indicate there was a low level of ability to use IT facilities, an inadequate number of professionals skilled in IT, a lack of technical capacity to sustain IT resources and the need for formal intensive training in IT applications (Bello et al 2004;Igben & Akobo 2001;Tiamiyu 2000;Komolafe-Opadeji 2009;Samuel et al 2004;Arora 2005). Our study also revealed that participants' previous training in IT were mostly through short courses or self-taught methods, which is similar to the findings of Ajuwon and Rhine (2008) where about a third of the participants first learnt to use ICT through self-teaching.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This might explain our findings which established that training in statistical analysis was the skill most sought-after by the participants (69.0 %). These findings coincide with various studies that indicate there was a low level of ability to use IT facilities, an inadequate number of professionals skilled in IT, a lack of technical capacity to sustain IT resources and the need for formal intensive training in IT applications (Bello et al 2004;Igben & Akobo 2001;Tiamiyu 2000;Komolafe-Opadeji 2009;Samuel et al 2004;Arora 2005). Our study also revealed that participants' previous training in IT were mostly through short courses or self-taught methods, which is similar to the findings of Ajuwon and Rhine (2008) where about a third of the participants first learnt to use ICT through self-teaching.…”
Section: Discussionsupporting
confidence: 86%
“…The majority had an email address, most of them possessed personal computers and some had access to the Internet. Although our study has not established whether those email addresses were in fact functional, our findings agree with several studies where most people valued IT for having improved productivity and efficiency (Subair & Kgankenna 2002;Royall et al 2005), but disagrees with other studies where there was reluctance to use IT, as people were unaware of its relevance and many had no access to the Internet and personal computers (Dorup 2004;Tiamiyu, 2000;Ameh, Kene & Ameh 2005). The majority of participants knew how to use IT applications, especially Microsoft Word, Excel and Access.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In Nigeria, researchers have studied the adoption and use of IT in different organizations and sectors. Odesanya and Ajiferuke (2000), for example, explored the use of IT by advertising agencies in Lagos, Tiamiyu (2000) studied the problems and impacts of using IT in Nigerian federal agencies, Fasheun-Motesho (2002) studied the adoption and growth of IT in Nigerian architectural firms, and Ehikhamenor (2003) examined the extent to which the Nigerian print media has been transformed by information and communication technologies (ICTs). Empirical studies of individual level use of IT have however been few.…”
Section: Factors Influencing It Use In Nigeriamentioning
confidence: 99%
“…Researchers in Nigerian universities engage in quality research, but lack of funds, especially through foreign exchange, and other infrastructural problems, makes it impossible to access the necessary literature. In a study conducted by Tiamiyu [23], the main three factors were listed that appear to account for this undesirable situation in Nigeria: 1. the dramatic decline in the nation's economic prosperity since the early 1980s, which has forced production and expenditure decisions in favour of necessities only; 2. the poor status of ICT-supporting infrastructure (electricity, telecommunications, etc. ), which makes it difficult to achieve an appreciable return on ICT investment; and 3. the international economic sanctions, which precipitated a poor investment climate which in turn prevented the free flow of funds, ideas and technologies that could have helped to modify or replace the entrenched traditional information management cultures with a modern ITC-oriented culture.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%